Multidimensional differences between athletes of endurance, strength, and intermittent sports: Body composition, diet, resting metabolic rate, physical activity, sleep quality, and subjective well-being - Rueda-Cordoba, M.; Martin-Olmedo, J. J.; Espinar, S.; Ruiz, J. R.; Jurado-Fasoli, L. (Nutrients, 2025)
Background/Objectives: Sports performance is influenced by a complex interplay of physical, physiological, and psychological factors, which differ across disciplines. Thus, this study aims to identify and compare the distinct multidimensional profiles (i.e., body composition, diet, resting metabolic rate, physical activity, sleep quality, and subjective well-being) of athletes from different sports disciplines (i.e., endurance, strength, and intermittent sports).